2020
DOI: 10.1155/2020/9629747
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Variations of MERS-CoV Infection among Suspected and Confirmed Cases: An Epidemiological Analysis of Laboratory-Based Data from Riyadh Regional Laboratory

Abstract: Introduction. Middle East respiratory syndrome coronavirus was first recognized in September 2012 in Saudi Arabia. The clinical presentations of MERS and non-MERS SARI are often similar. Therefore, the identification of suspected cases that may have higher chances of being diagnosed as cases of MERS-CoV is essential. However, the real challenge is to flag these patients through some demographic markers. The nature of these markers has not previously been investigated in Saudi Arabia, and hence, this study aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(31 reference statements)
1
10
1
Order By: Relevance
“…Altamimi et al. reported 119 confirmed cases during 2017 in the capital and central region of Saudi Arabia, in 2016 the number of cases was 48.7% higher than 2017 and 25.4% lower than 2015 reported cases these findings were supported in other researches [ 21 , 24 ]. Although SARS-CoV-2 is more transmissive when compared to SARS-CoV and MERS-CoV has higher severity and mortality, according to available data and such findings were confirmed in Yi et al.…”
Section: Discovery and Similaritiessupporting
confidence: 53%
See 2 more Smart Citations
“…Altamimi et al. reported 119 confirmed cases during 2017 in the capital and central region of Saudi Arabia, in 2016 the number of cases was 48.7% higher than 2017 and 25.4% lower than 2015 reported cases these findings were supported in other researches [ 21 , 24 ]. Although SARS-CoV-2 is more transmissive when compared to SARS-CoV and MERS-CoV has higher severity and mortality, according to available data and such findings were confirmed in Yi et al.…”
Section: Discovery and Similaritiessupporting
confidence: 53%
“…A study was carried out during 2017 by Altamimi et al. in Saudi Arabia mentioned that the most MERS-CoV infected cases were recorded during summer [ 21 ]. Also, earlier study observed that the maximum number of MERS-CoV occurrence and mortalities were not recorded in the winter, but in the spring between the end of April and the beginning of May [ 22 ].…”
Section: Discovery and Similaritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the fact that this strain has never been encountered in Africa, just as the strain of SARS-CoV-2 (before now) has made the scare less anticipated. However, even though virtually 80% of the recounted MERS-CoV cases have been in Saudi Arabia alone, about 2519 cases and 866 associated fatalities between 2012 and 31st January 2020 ( https://www.who.int/csr/don/24-february-2020-mers-saudi-arabia/en/ ), makes it an important infection Africa must be wary of (Altamimi et al 2020 ). According to WHO, several travel-related cases have already befallen Greece, Germany, France, Philippines, the United Kingdom, Malaysia, Egypt, Italy, the Netherlands, Turkey, South Korea, Algeria, Austria, China, and the United States (WHO 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to WHO, several travel-related cases have already befallen Greece, Germany, France, Philippines, the United Kingdom, Malaysia, Egypt, Italy, the Netherlands, Turkey, South Korea, Algeria, Austria, China, and the United States (WHO 2019 ). To date, the major plague of MERS-CoV, after Saudi Arabia, happened in South Korea from May through July of 2015, with 186 stated cases and 39 deaths to make a 21% case fatality rate (Altamimi et al 2020 ). It will, therefore, be instructive, for Africa to brace up to the challenge of a future possibility of a MERS-CoV outbreak.…”
Section: Resultsmentioning
confidence: 99%